2015
DOI: 10.1186/s12871-015-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of measured and calculated serum osmolality during the infusion of mannitol or hypertonic saline in patients after craniotomy: a prospective, double-blinded, randomised controlled trial

Abstract: BackgroundMannitol and hypertonic saline are used to ameliorate brain edema and intracranial hypertension during and after craniotomy. We hypothesized that the agreement of measured and calculated serum osmolality during the infusion of hypertonic saline would be better than mannitol. The objective was to determine the accuracy of serum osmolality estimation by different formulas during the administration of hyperosmolar agent.MethodsA prospective, randomized, double-blinded, controlled trial was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…[21] We confirmed that the medication were initiated with the admission to PICU in a majority of the children, and the duration to reach the target serum osmolality extended to 8.5 h (3.5-40 h). In the prospective randomized double blind study, Li et al [22] demonstrated the serum osmolality for mannitol and 3% NaCl infusion was as 292.4±9.1 mosm/L and 294.1±6.6 mosm/L, respectively, and both these values were below the threshold levels at 6 h. As shown by Francony et al, [23] 20% Mannitol and 7.4% NaCl infusions elevated serum osmolality only by 2%. Delays in achieving the target osmolality result in prolonged exposure to elevated ICP which are directly related to negative prognosis, and a multidisciplinary approach towards TBI management (medical staff responding in the field, ER physicians, and neurosurgeons) contributes to positive prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…[21] We confirmed that the medication were initiated with the admission to PICU in a majority of the children, and the duration to reach the target serum osmolality extended to 8.5 h (3.5-40 h). In the prospective randomized double blind study, Li et al [22] demonstrated the serum osmolality for mannitol and 3% NaCl infusion was as 292.4±9.1 mosm/L and 294.1±6.6 mosm/L, respectively, and both these values were below the threshold levels at 6 h. As shown by Francony et al, [23] 20% Mannitol and 7.4% NaCl infusions elevated serum osmolality only by 2%. Delays in achieving the target osmolality result in prolonged exposure to elevated ICP which are directly related to negative prognosis, and a multidisciplinary approach towards TBI management (medical staff responding in the field, ER physicians, and neurosurgeons) contributes to positive prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…This assumption was supported by the fact that calculated efOsmol was significantly lower in foals with neurological signs compared with those without. Ideally, efOsmol is measured, rather than calculated, but in most clinical situations good correlation between both can be assumed . Exceptions are cases with the presence of unidentified osmoles that remain undetected unless osmolality is measured .…”
Section: Discussionmentioning
confidence: 99%
“…Typical sodium goals for lowering elevated ICPs range from 145 to 155 mmol/L, which correlates to the estimated 10 mOsmol/ kg difference needed to create the gradient necessary to cause fl uid shifts. 14 If these sodium values are exceeded or are achieved too rapidly, patients are at risk for seizures, altered mental status, and potentially central pontine myelinolysis. Recently, data have suggested that chloride may have a larger effect on patients being treated with hypertonic saline than originally thought.…”
Section: Hypertonic Salinementioning
confidence: 99%